Consistent Left-Right Reversals for Visual Path Integration in Virtual Reality: More than a Failure to Update One's Heading? - Riecke, Bernhard E. (Presence: Teleoperators and Virtual Environments, 2008)
Even in state-of-the-art virtual reality (VR) setups, participants often feel lost when navigating through virtual environments. In VR applications and psychological experiments, such disorientation is often compensated for by extensive training. Here, two experimental series investigated participants' sense of direction by means of a rapid point-to-origin paradigm without any performance feedback or training. This paradigm allowed us to study participants' intuitive spatial orientation in VR while minimizing the influence of higher cognitive abilities and compensatory strategies. After visually displayed passive excursions along one- or two-segment trajectories, participants were asked to point back to the origin of locomotion “as accurately and quickly as possible.” Despite using an immersive, high-quality video projection with a 84° × 63° field of view, participants' overall performance was rather poor. Moreover, about 40% of the participants exhibited striking qualitative errors, namely left-right reversals—despite not misinterpreting the visually simulated turning direction. Even when turning angles were announced in advance to obviate encoding errors due to misperceived turning angles, many participants still produced surprisingly large systematic and random errors, and perceived task difficulty and response times were unexpectedly high. Careful analysis suggests that some, but not all, of the left-right inversions can be explained by a failure to update visually displayed heading changes. Taken together, this study shows that even an immersive, high-quality video projection system is not necessarily sufficient for enabling natural and intuitive spatial orientation or automatic spatial updating in VR, even when advance information about turning angles was provided. We posit that investigating qualitative errors for basic spatial orientation tasks using, for example, rapid point-to-origin paradigms can be a powerful tool for evaluating and improving the effectiveness of VR setups in terms of enabling natural and unencumbered spatial orientation and performance. We provide some guidelines for VR system designers.
Keywords: Riecke; Riecke_2008; bernhard-riecke; iSpaceWeb; journalPaper; point-to-origin